Revolusi Biru dan Perubahan-Perubahan Alat Tangkap pada Nelayan Desa Jujun, Kecamatan Keliling Danau, Kabupaten Kerinci (1970-2022) - Putma, Tejja Ari; Midawati, Midawati; Nopriyasman, Nopriyasman (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This study examines the Blue Revolution and its impact on changes in fishing gear among fishermen in Jujun Village, who have shifted from using traditional to modern fishing methods—a trend also observed among fishermen living around Lake Kerinci. The purpose of this research is to analyze the implementation of the Blue Revolution in Keliling Danau Sub-district. Employing historical methods, the study follows several stages, including data collection (heuristics), source criticism, data interpretation, and historiography. The findings reveal that since the introduction of the Blue Revolution in 1970, fishermen in Jujun Village have experienced significant advancements in fishing gear. This progress became increasingly evident by 2010, marked by the adoption of more modern technologies such as lighted bagan tancap, iron fish traps, and motorboats. The study concludes that the transformation initiated by the Blue Revolution has continuously influenced the development and modernization of fishing practices among the fishermen in Jujun Village.